Skin ulceration and inguinal lymphadenopathy as a symptom of a rare tick-borne disease - Janocha-Litwin, Justyna; Szymanek-Pasternak, Anna; Zacharczuk, Katarzyna; Wolaniuk, Natalia; Śliwińska, Magdalena; Simon, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
A 69-year-old man with suspected Lyme disease visited an infectious disease specialist in the outpatient clinic. 3 weeks earlier, he felt a painful bite in his left buttock, caused by a tick that was later removed. After several days, significant weakness, drowsiness, chills and muscle pains occurred, followed by a 2 cm red inflammatory infiltration appearing in the location of the bite with crust over the ulceration and enlarged left inguinal lymph nodes (Figure 1 A).